2021
DOI: 10.1186/s13213-020-01611-7
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based proteomic analysis reveals the molecule mechanism of reducing higher alcohols in Chinese rice wine by nitrogen compensation

Abstract: Purpose Higher alcohol is a by-product of the fermentation of wine, and its content is one of the most important parameters that affect and are used to appraise the final quality of Chinese rice wine. Ammonium compensation is an efficient and convenient method to reduce the content of higher alcohols, but the molecule mechanism is poorly understood. Therefore, an iTRAQ-based proteomic analysis was designed to reveal the proteomic changes of Saccharomyces cerevisiae to elucidate the molecular me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…These results suggest that ammonium compensation can effectively decrease FAs in Chinese rice wine. The molecular mechanism of ammonium compensation in reducing the content of FAs involved the reversal of the carbon flow that would have gone to the FA synthesis pathway to the TCA cycle, which thereby decreased the content of FAs [ 48 ]. The effects of nitrogen compensation on YB-12 in the process of rice wine fermentation should be determined in the future.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that ammonium compensation can effectively decrease FAs in Chinese rice wine. The molecular mechanism of ammonium compensation in reducing the content of FAs involved the reversal of the carbon flow that would have gone to the FA synthesis pathway to the TCA cycle, which thereby decreased the content of FAs [ 48 ]. The effects of nitrogen compensation on YB-12 in the process of rice wine fermentation should be determined in the future.…”
Section: Resultsmentioning
confidence: 99%
“…This would rely on the ecological modifications performed by the AM as a result of the presence of dangerous metals. The mycorrhizal parasite Glomus caledonium seems to be a good choice for bioremediating soil polluted with massive steel [258,259].…”
Section: Bioremediationmentioning
confidence: 99%
“…The main higher alcohols in Baijiu include n-propanol, isobutanol, isoamyl alcohol, 2-methylbutanol and β-phenylethanol, which are the main metabolites of Saccharomyces cerevisiae [7]. Studies have shown that the Ehrlich and Harris pathways are the two main metabolic pathways of higher alcohols [8,9]. The mechanism of the Ehrlich pathway is to catalyze the transamination of branched-chain amino acids, such as valine, leucine and isoleucine to produce the corresponding higher alcohols by decarboxylation and dehydrogenation of 2-oxoisovalarate, 4-methyl-2-oxopentanoate and 3-methyl-2-oxopentanoate, respectively [10].…”
Section: Introductionmentioning
confidence: 99%